Microelectronics - Whitaker, Jerry C. (Talor & Francis, 2006)
This book focuses on the materials, devices, and applications of microelectronics technology. It details the IC design process and VLSI circuits, including gate arrays, programmable logic devices and arrays, parasitic capacitance, and transmission line delays. Coverage ranges from thermal properties and semiconductor materials to MOSFETs, digital logic families, memory devices, microprocessors, digital-to-analog and analog-to-digital converters, digital filters, and multichip module technology. Expert contributors discuss applications in machine vision, ad hoc networks, printing technologies, and data and optical storage systems. The book also includes defining terms, references, and suggestions for further reading. This edition features two new sections on fundamental properties and semiconductor devices. With updated material and references in every chapter, Microelectronics, Second Edition is an essential reference for work with microelectronics, electronics, circuits, systems, semiconductors, logic design, and microprocessors.